Langkauas (Zingiber zerumbet Linn. Smith) extract as meat (rump) tenderizer - Parrone, Sarah Flandez; De Leon, Sonia Y. (1993.)
Addition of Langkauas (Zingiber zerumbet Linn. Smith) extract at levels of 0.1 mg and 0.2 mg in 35 grams of meat (rump) produced a significant effect on the tenderness of meat roasts. Statistical analysis showed that such concentrations of extract applied on meat slices for at least 60 minutes of treatment at 28°C and at -5°C enhanced tenderness significantly at the 5% level; however, measurement of the texture using the Humboldt penetrometer showed that the concentration level of 0.2 mg of extract per 25 grams of meat with treatment time of 90 minutes at -5°C produced tender meat roasts.
Thesis (BSFT)--University of the Philippines Diliman.
Keywords: Meat tenderizer; Langkauas